2022
DOI: 10.1158/1055-9965.epi-21-0977
|View full text |Cite
|
Sign up to set email alerts
|

High Prediagnosis Inflammation-Related Risk Score Associated with Decreased Ovarian Cancer Survival

Abstract: Background: There is suggestive evidence that inflammation is related to ovarian cancer survival. However, more research is needed to identify inflammation-related factors that are associated with ovarian cancer survival and to determine their combined effects.Methods: This analysis used pooled data on 8,147 women with invasive epithelial ovarian cancer from the Ovarian Cancer Association Consortium. The prediagnosis inflammation-related exposures of interest included alcohol use; aspirin use; other nonsteroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 68 publications
(59 reference statements)
1
0
0
Order By: Relevance
“…Evaluation of the prognostic value of the presence of symptoms in the present study revealed that all asymptomatic patients with OEC and OCCC survived without recurrence, whereas all patients who showed recurrence and died of the disease presented with symptoms. Although tumor progression rather than symptomatology seems to be a major factor in their poor prognoses, some reported that prediagnosis high in ammation associated with decreased ovarian cancer survival, which may be compatible with our results [27,28]. The presence of symptoms may be a prognostic factor; however, the bias that asymptomatic cases receive early treatment cannot be denied.…”
Section: Discussionsupporting
confidence: 88%
“…Evaluation of the prognostic value of the presence of symptoms in the present study revealed that all asymptomatic patients with OEC and OCCC survived without recurrence, whereas all patients who showed recurrence and died of the disease presented with symptoms. Although tumor progression rather than symptomatology seems to be a major factor in their poor prognoses, some reported that prediagnosis high in ammation associated with decreased ovarian cancer survival, which may be compatible with our results [27,28]. The presence of symptoms may be a prognostic factor; however, the bias that asymptomatic cases receive early treatment cannot be denied.…”
Section: Discussionsupporting
confidence: 88%